DISEÑO Y CONSTRUCCION DE UN SISTEMA DE FLOTACION POR AIRE DISUELTO, DE EFLUENTES LIQUIDOS, A NIVEL DE LABORATORIO - Pizarro-Cabrera, R. (2000)
This work concerns the design and construction of a flotation equipment - laboratory size - for the treatment of waste water of the fishmeal industry.